Introduction to experimental nonlinear dynamics : - Virgin, Lawrence N. (Cambridge University Press, 2000)
Nonlinear dynamics and chaos have a role in virtually every area of science and engineering and so have become very active fields of study and research. This book uses an extended case study--an experiment in mechanical vibration--to introduce and explore the subject of nonlinear behavior and chaos. Beginning with a review of basic principles, the text then describes a cart-on-a-track oscillator and shows what happens when it is gradually subjected to greater excitation, thereby encountering the full spectrum of nonlinear behavior, from simple free decay to chaos. Students and practicing engineers will find this book a lively, accessible introduction to the complex world of nonlinear dynamics.